Pengembangan Kualitas Vokal dan Harmoni melalui Latihan Koor di Gereja dalam Program MBKM Mandiri di SMPK St. Theresia Kupang - Yosefina Arina Bauk; Veronika Alexandra Tonbesi; Anselmus Tupen Knoten; Maria Reneldi Guyu Tiku; Stefanus Lio (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
The MBKM (Merdeka Belajar Kampus Merdeka) program is mandatory for every student at the Faculty of Teacher Training and Education, Universitas Katolik Widya Mandira Kupang. The program aims to share new knowledge and provide direct experience through field activities that can enhance the competence of prospective teachers. One of the MBKM activities outside the classroom is choir training. The community service is conducted through assisting choir practice for students of SMPK St. Theresia Kupang at the Catholic Church of Santo Fransiskus Aisi BTN Kolhua, located at JL. Fetor Funay No. 8, Kolhua, Maulafa Subdistrict, Kupang City, East Nusa Tenggara. Choir training is a form of musical art that requires good teamwork and coordination among members to achieve perfect harmony. This article aims to explore effective methods in choir training, with the church as the venue for the students’ activities to fulfill the KKN or MBKM program based on extracurricular activities to enhance vocal quality and harmony. This research was conducted through observation, interviews with the choir trainer, and active participation in training sessions, focusing on Vocal techniques (Pitch, Phrasing, Harmonization, Articulation, and Intonation) and Expression (Tempo, Dynamics, Interpretation, Rhythm, and Resonance). The results of the study show that vocal warm-ups, clear voice division, and regular evaluations play a crucial role in the success of choir practice. By applying these methods, the choir group was able to achieve better musical quality. Additionally, this program successfully fostered social responsibility and teamwork. In conclusion, this extracurricular activity positively impacts the development of vocal skills and social awareness within the learning environment.